Towards an indigenous (Xhosa) South African biblical scholarship - Mtshiselwa, Ndikho (Old Testament essays, 2011)
Whiteness that continues to influence indigenous biblical interpretation is problematic in South African biblical scholarship. The purpose of this article is to further the debate on whiteness that results into a paradigm shift from an interpretation influenced by whiteness to an indigenous (Xhosa) biblical interpretation, blackness. While whiteness is explored in this article, a process of reading the Bible from an indigenous (Xhosa) perspective is advocated for, tested and illustrated by utilizing a Xhosa-constructed song to unlock and reconstruct a meaning of an ancient text (Mark 9:4). The findings presented in this article demonstrate that historical and literary criticisms are problematic, that they express impediments to the emancipation of blackness and shows how the usage of European church songs that supposedly unlock the meaning of ancient texts reveals whiteness's continuing influence in current South African biblical scholarship. A reconfiguration of the Hebrew Bible's Moses and Elijah with the help of an indigenous (Xhosa) song, demonstrates how blackness similarly unlocks the meaning of an ancient text, which is not shaded by whiteness.